2020
DOI: 10.1177/0840470420942262
|View full text |Cite
|
Sign up to set email alerts
|

The Team Assessment of Self-Management Support (TASMS): A new approach to uncovering how teams support people with chronic conditions

Abstract: Canadian and other healthcare systems are adopting primary care models founded on multidisciplinary, team-based care. This paper describes the development and use of a new tool, the Team Assessment of Self-Management Support (TASMS), designed to understand and improve the self-management support teams provide to patients with chronic conditions. Team Assessment of Self-Management Support captures the time providers spend supporting seven different types of self-management support (process strategies, resources… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…The multidisciplinary team approach is a treatment domain that optimizes the health of patients with chronic diseases [ 34 ]. Promoting a multidisciplinary team approach is crucial for coordinating the health care system and aiding patients in self-management [ 35 ]. However, our research revealed that the majority of mHealth apps did not incorporate a multidisciplinary team to support health management.…”
Section: Discussionmentioning
confidence: 99%
“…The multidisciplinary team approach is a treatment domain that optimizes the health of patients with chronic diseases [ 34 ]. Promoting a multidisciplinary team approach is crucial for coordinating the health care system and aiding patients in self-management [ 35 ]. However, our research revealed that the majority of mHealth apps did not incorporate a multidisciplinary team to support health management.…”
Section: Discussionmentioning
confidence: 99%
“…Developing accurate and comprehensive measures to assess self-care and self-management by individuals and support across health services has the potential to promote integrated and personalized care and support for older people with multimorbidity (Keddy et al, 2021;Nichols et al, 2020;Shepherd et al, 2022;WHO, 2015). Personalized care planning, defined as a series of discussions between a patient and a health professional to clarify goals, options, and preferences and develop an agreed plan of action, embodies the core principles of person-centeredness and shared decision-making (Coulter et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Assigning disciplinary case managers based on patient needs and provider scope of practice are two examples. This work could be strengthened using the Team Assessment of Self-Management Strategies (TASMS), also based on the TEDSS framework, to better understand the types of self-management support teams provide [ 54 ].…”
Section: Discussionmentioning
confidence: 99%